2018
DOI: 10.1177/2050312118807624
|View full text |Cite
|
Sign up to set email alerts
|

The abortion and mental health controversy: A comprehensive literature review of common ground agreements, disagreements, actionable recommendations, and research opportunities

Abstract: The abortion and mental health controversy is driven by two different perspectives regarding how best to interpret accepted facts. When interpreting the data, abortion and mental health proponents are inclined to emphasize risks associated with abortion, whereas abortion and mental health minimalists emphasize pre-existing risk factors as the primary explanation for the correlations with more negative outcomes. Still, both sides agree that (a) abortion is consistently associated with elevated rates of mental i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
83
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(91 citation statements)
references
References 233 publications
(738 reference statements)
5
83
0
3
Order By: Relevance
“…For example, a study that investigated the association between abortion and risk of subsequent depression in pregnant women showed that women with a history of abortion were more likely to have depression (AOR = 3.5; 95% CI 2.06.1) [47]. In a comprehensive literature review of 2018, abortion has been associated with higher rates of mental health problems when compared to women without a history of abortion [48,49]. Further, evidence from a prospective cohort study also showed a 30% relative increase in the rate of depression among women who reported a history of abortion when compared to those who did not [50].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study that investigated the association between abortion and risk of subsequent depression in pregnant women showed that women with a history of abortion were more likely to have depression (AOR = 3.5; 95% CI 2.06.1) [47]. In a comprehensive literature review of 2018, abortion has been associated with higher rates of mental health problems when compared to women without a history of abortion [48,49]. Further, evidence from a prospective cohort study also showed a 30% relative increase in the rate of depression among women who reported a history of abortion when compared to those who did not [50].…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] These findings demonstrating that low-income women who have abortions are more likely to have more overall pregnancies, including more subsequent abortions, would tend to support the body of evidence indicating that abortion is associated with greater subsequent reproductive health risks. 13,14 Abortion decreases the likelihood of a birth in any subsequent pregnancy. More than 60% of surveyed women seeking an abortion indicate that they had not completed their childbearing.…”
Section: Discussionmentioning
confidence: 99%
“…18 Guidelines in other jurisdictions state that women should have access to objective information and counselling about their pregnancy options in the case of unwanted pregnancy. 26 While some studies show that women may experience mental health problems following abortion, [27][28][29][30] others have challenged this. 31,32 In any case, support techniques for a more informed choice are needed.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%